2022
DOI: 10.1002/anie.202205493
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(II)‐Catalyzed C(sp3)−H Diamination of Arylcyclobutanes

Abstract: Activated by multiple consecutive oxidative radical‐polar crossover and desaturation processes, the selective diamination of arylcyclobutanes, which is difficult to perform by classical metallonitrene C−H insertion, was achieved in a short time by rhodium(II) catalysis using N‐fluorobenzenesulfonimide (NFSI) as the oxidant and nitrogen source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…On the basis of the results presented above and previous research, , a palusible reaction mechanism has been proposed (Scheme d). The catalytic cycle starts with the NFSI-oxidized Rh­(II) catalysts, generating the Rh 2 (II,III)-ligated •NSI species [Rh 2 (II,III)-NSI], followed by the Rh 2 (II,III)-NSI species capturing the benzyl hydrogen in the cyclopentane substrate to form benzyl radical A .…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…On the basis of the results presented above and previous research, , a palusible reaction mechanism has been proposed (Scheme d). The catalytic cycle starts with the NFSI-oxidized Rh­(II) catalysts, generating the Rh 2 (II,III)-ligated •NSI species [Rh 2 (II,III)-NSI], followed by the Rh 2 (II,III)-NSI species capturing the benzyl hydrogen in the cyclopentane substrate to form benzyl radical A .…”
mentioning
confidence: 83%
“…Our group worked on studies of radical relay reactions and developed the single-electron oxidation reactions of the classical Rh­(II) catalyst previously used for nitrene transfer . Recently, the diamination reaction of arylcyclobutanes, which involves nine consecutive steps in a short period of time, has been successfully achieved using the rhodium­(II)/ N -fluorobenzenesulfonimide [Rh­(II)/NFSI] catalytic system (Scheme b) . During the study, we found that the Rh­(II)/NFSI catalytic system can efficiently achieve the desaturation activation of cycloalkanes in the presence of a base.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the whole, the reaction mechanism includes three cycles, i.e., dehydration, 1 st amination and 2 nd amination. With this strategy, they also developed an efficient direct diamination protocol for arylcyclobutanes (Scheme 69) 117 and the desaturative [3 + 2] tandem cyclization of arylcycloalkanes with β-dicarbonyls (Scheme 70). 118 In the course of research, Wang and coworkers also found an interesting one-step route for allylic 1,3-diamination (Scheme 71).…”
Section: Dirhodium In Radical Oxidation and Diaminationmentioning
confidence: 99%
“…Hence, the development of simultaneous electrochemical methodologies for direct, efficient, and selective multiple C–H functionalization in a greener, more general, and economic way, facilitating potential practical applications, is still scarce and highly desirable yet challenging. 12 Notably, Lambert and co-workers reported an elegant electrophotocatalytic diamination of vicinal C(sp 3 )–H bonds by successive Ritter-type aminations, 13 using a combination of light and electrical energy, 14 and this strategy was also further successfully applied to the oxygenation of multiple adjacent C(sp 3 )–H bonds, 15 which are elegant examples of synthesizing multi-functionalized compounds by electrophotocatalysis with the potential for further applications.…”
Section: Introductionmentioning
confidence: 99%